PEMBELAJARAN MENULIS PUISI DENGAN MENGGUNAKAN TEKNIK PEMODELAN (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Abstract Writing poetry is an activity to develop literary skills that requires a creative thinking process. Through writing poetry activities, students will be able to develop ideas, feelings, and thoughts to produce beautiful language symbols. Writing poetry is included in creative writing. In writing poetry, one cannot immediately write poetry but must go through several processes, one of which is continuous learning. One of the techniques used in learning to write new poetry is modeling techniques. This technique was chosen to assist students in learning to write poetry by using models in the form of poetry texts. With the existence of models and examples that can be imitated, it will be a new innovation in learning poetry and can help overcome students' difficulties in writing poetry. Keywords: learning to write; poetry; modeling techniques